A Review of Digital, Social, and Mobile Technologies in Health Professional Education. Issue 3 (2017) - Curran, Vernon; Matthews, Lauren; Fleet, Lisa; Simmons, Karla; Gustafson, Diana L.; Wetsch, Lyle
Abstract : Introduction: Digital, social, and mobile technologies (DSMTs) can support a wide range of self-directed learning activities, providing learners with diverse resources, information, and ways to network that support their learning needs. DSMTs are increasingly used to facilitate learning across the continuum of health professional education (HPE). Given the diverse characteristics of DSMTs and the formal, informal, and nonformal nature of health professional learning, a review of the literature on DSMTs and HPE could inform more effective adoption and usage by regulatory organizations, educators, and learners. Methods: A scoping review of the literature was performed to explore the effectiveness and implications of adopting and using DSMTs across the educational continuum in HPE. A data extraction tool was used to review and analyze 125 peer-reviewed articles. Common themes were identified by thematic analysis. Results: Most articles (56.0%) related to undergraduate education; 31.2% to continuing professional development, and 52.8% to graduate/postgraduate education. The main DSMTs described include mobile phones, apps, tablets, Facebook, Twitter, and YouTube. Approximately half of the articles (49.6%) reported evaluative outcomes at a satisfaction/reaction level; 45.6% were commentaries, reporting no evaluative outcomes. Most studies reporting evaluative outcomes suggest that learners across all levels are typically satisfied with the use of DSMTs in their learning. Thematic analysis revealed three main themes: use of DSMTs across the HPE continuum; key benefits and barriers; and best practices. Discussion: Despite the positive commentary on the potential benefits and opportunities for enhancing teaching and learning in HPE with DSMTs, there is limited evidence at this time that demonstrates effectiveness of DSMTs at higher evaluative outcome levels. Further exploration of the learning benefits and effectiveness of DSMTs for teaching and learning in HPE is warranted.